Comparison of PUCAI Score in Mesalazine-Treated Children with Ulcerative Colitis - Nadia Chairunnisa; Juwita Pratiwi; Ninung Rose Diana Kusumawati (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Ulcerative colitis is a chronic idiopathic inflammatory bowel disease (IBD) characterized by intestinal inflammation confined to the superficial mucosal layer. Mesalazine, a 5-aminosalicylic acid (5-aminosalicylic, or 5-ASA) compound, is most often used as first-line therapy for mild to moderate ulcerative colitis. The Pediatric Ulcerative Colitis Activity Index (PUCAI) is a non-invasive multi-item measure that has been shown to be valid, reliable, and responsive to short-term changes in several clinical trials and cohort studies. Therefore, this study aims to compare the PUCAI scores in children with ulcerative colitis who received mesalazine therapy to those who did not. Methods: We performed a retrospective database analysis of 12 patients, who were diagnosed with ulcerative colitis at Dr. Kariadi General Hospital, Semarang, Indonesia in a span of 1 year. We included all cases of pediatric patients with ulcerative colitis, then we divided them into 2 groups, the group receiving mesalazine therapy and the group who did not. We monitored the development of PUCAI scores before and after treatment. Results: The number of samples in this study was 12 samples. All sample data were taken based on data from pediatric gastroenterohepatology patients diagnosed with colitis ulcerative based on pathology anatomy results, who were treated in the pediatric ward of RSUP Dr. Kariadi Semarang. From the result of the paired t-test, there was a significant decrease in PUCAI score in patients who received Mesalazine, (p = 0.007), while those who did not receive mesalazine, did not show any significant decrease in PUCAI score. Conclusion: Ulcerative colitis (UC) is a chronic relapsing inflammatory condition. UC is often treated with mesalazine as the first-line treatment. The use of the PUCAI score is an appropriate tool to determine the progression of this disease. Based on the data obtained, the administration of mesalazine therapy in children with ulcerative colitis can improve PUCAI scores compared to children who do not receive mesalazine therapy.